The relative contribution of the most important signs of motor and functional performance of some of the offensive skills of football players ages ( 20-30 ) years - A. D. Wissam Hameed A. D. Ali Asfour (الرياضة المعاصرة)
A search on the four-door, as it contained the first door on the front and the importance of research, and touched a researcher of the importance of testing and measurement in the field of sports, especially football game as well as the focus was on the most important motor and functional capacity and some offensive skills, came the importance of research to identify the percentage contribution of the motor and functional capacity the performance of the offensive skills of footballers applicants, either the research problem lies on the need to know the coaches percentage contribution of the motor and functional capacity to perform some offensive skills in football, either the areas of research included the human domain that represents my players advanced in Maysan province for the sports season (2016 -2017) , temporal area and determine the duration of the (06/25/2017) to very (07/30/2017), while the domain spatial golf clubs Maysan province.